Poltergeist activity and Andrés Venier's case: some phenomenological, neuropsychological, and psychodynamical issuess - Parra, Alejandro (2005)
In this article the author discusses the phenomenology, neuropsychological and psychodynamical issues about poltergeist activity, with main emphasis on Andrés Venier’s case, of Río Tercero, province of Córdoba, Argentina. The phenomenon seems to be caused by unconscious psychokinesis (mind over matter). These events have been reported since antiquity. Its phenomenology is described in terms of throwings and displacements of objects, noises, lights, apparitions and foul smellings. Besides, poltergeists are capable of interference with electronic equipment while other reports include somatic lesions.